2023
DOI: 10.1155/2023/8938674
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of MicroRNA-23-27-24 Clusters Exhibits the Impairment of Myelination in the Central Nervous System

Abstract: Several microRNAs (miRNAs), including miR-23 and miR-27a have been reportedly involved in regulating myelination in the central nervous system. Although miR-23 and miR-27a form clusters in vivo and the clustered miRNAs are known to perform complementary functions, the role of these miRNA clusters in myelination has not been studied. To investigate the role of miR-23-27-24 clusters in myelination, we generated miR-23-27-24 cluster knockout mice and evaluated myelination in the brain and spinal cord. Our results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 46 publications
0
8
1
Order By: Relevance
“…Previous studies have reported the expression of miR-23a/b clusters in the liver, lungs, skeletal muscles, and CNS [14,18,19]. In this context, the present study assessed changes in the expression of these clusters in the organs of myelin-specific miR-23a/b cluster-deficient mice.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Previous studies have reported the expression of miR-23a/b clusters in the liver, lungs, skeletal muscles, and CNS [14,18,19]. In this context, the present study assessed changes in the expression of these clusters in the organs of myelin-specific miR-23a/b cluster-deficient mice.…”
Section: Discussionmentioning
confidence: 92%
“…In our previous study using mice systemically deficient in miR-23a/b clusters, differences were noted between KO and control mice in the hanging wire test but not in the balance beam test [14]. The balance beam test described in a previous study used a 10 mm wide and 50 cm long beam.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations